2011
DOI: 10.1002/ibd.21421
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence rate of clostridium difficile infection in hospitalized pediatric patients with inflammatory bowel disease

Abstract: CD infection in patients with IBD results in a higher rate of recurrence and is associated with higher morbidity than the general population. Patients with IBD often required hospitalization and escalation of therapy following infection with CD, suggesting that CD resulted in increased severity of IBD disease. In addition, IBD patients were more likely develop community-acquired CD, while the control patients developed nosocomial infections, indicating a higher susceptibility to CD infection in patients with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 19 publications
0
62
3
1
Order By: Relevance
“…3 Nevertheless, CDI can be a trigger of IBD activity and testing for presence of C. difficile is part of a standard evaluation of severe IBD colitis. 4,5 Notably, several studies have found that IBD patients with CDI have worse outcomes, including prolonged length of hospitalization, intensive care unit admissions, rates of colectomy, post-surgical complications, post-colectomy pouch failure, and death. [6][7][8][9][10] One of the most common problems associated with CDI in all patients is recurrence of the infection following antibiotic therapy.…”
Section: Concurrence Of Inflammatory Bowel Disease (Ibd) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Nevertheless, CDI can be a trigger of IBD activity and testing for presence of C. difficile is part of a standard evaluation of severe IBD colitis. 4,5 Notably, several studies have found that IBD patients with CDI have worse outcomes, including prolonged length of hospitalization, intensive care unit admissions, rates of colectomy, post-surgical complications, post-colectomy pouch failure, and death. [6][7][8][9][10] One of the most common problems associated with CDI in all patients is recurrence of the infection following antibiotic therapy.…”
Section: Concurrence Of Inflammatory Bowel Disease (Ibd) Andmentioning
confidence: 99%
“…The problem of CDI recurrence is even greater in patients with underlying IBD. 5,11 Antibiotics fail to eradicate the spores of C. difficile, and can perpetuate the cycles of CDI recurrence by causing progressive suppression of indigenous gut microbiota. 12 Thus, patients can develop recurrent CDI (rCDI) syndrome, which is characterized by indefinite cycles of antibiotic treatments and CDI recurrences.…”
Section: Concurrence Of Inflammatory Bowel Disease (Ibd) Andmentioning
confidence: 99%
“…Recurrence of CDI can occur in 20-30% after initial infection, with the frequency of recurrence rising further after subsequent infections (19)(20)(21). Risk factors for recurrent CDI in children include IBD (22,23), malignancy, recent surgery, and the number of antibiotic exposures by class (19). FMT has been shown to be more effective than antibiotics for recurrent CDI in adults (12,13); van Nood et al (12) showed a cure rate of 81% after FMT compared with 31% with vancomycin alone and Cammarota et al (13) had similar results with resolution of CDI in 90% of those treated with FMT compared with 26% treated with vancomycin.…”
Section: Fmt For Recurrent CDI In Childrenmentioning
confidence: 99%
“…The pathophysiology underlying the association of CDI with these lesserknown yet emerging cohorts remains unclear. Other risk factors that have been linked with CDI are age greater than 65 years, proton pump inhibitor use, prolonged hospital stay, and severe comorbidities such as inflammatory bowel disease and chronic renal disease [19][20][21][22][23][24][25][26][27]. Fig.…”
Section: Clostridium Difficile Infection (Cdi)mentioning
confidence: 99%